Obravnava klasičnih literarnih besedil pri pouku slovenščine kot tujega jezika - Klemen, Matej (Jezik in slovstvo, 2022)
This paper deals with the question of how to include literary classics in the Slovene foreign language classroom. It outlines the specific qualities of such texts, and offers justification as to why their introduction merits a thorough and organised approach. The paper analyses tasks based on Ivan Cankar's works in textbooks for students of Slovene as a foreign language. Alongside an excerpt from Cankar's novel Na klancu (On the Slope), the paper suggests a number of activities for developing communicative language skills as well as an appreciation of the literature's aesthetic qualities.
Keywords: Cankar, Ivan; klasična literarna dela; literary classics; methodology; metodika; Slovene as a foreign language; slovenščina kot tuji jezik